2014
DOI: 10.1097/mat.0000000000000061
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation for Ventricular Tachyarrhythmias in Patients Supported by Continuous-Flow Left Ventricular Assist Devices

Abstract: Ventricular arrhythmias (VAs) are common after implantation of a left ventricular assist device (LVAD) and in a subset of patients may be refractory to medication. Morbidity from VA in this population includes right ventricular failure (RVF). We sought to evaluate the efficacy of catheter ablation for VA in patients with LVAD. A retrospective analysis of patients supported by continuous-flow LVAD referred for catheter ablation of ventricular tachycardia (VT) between 2008 and the present was performed. Seven pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 21 publications
0
19
0
1
Order By: Relevance
“…Indeed, patients in the RHF group more frequently required re-admission due to cardiac tachyarrhythmia that may lead to worsening right ventricular function. 17 Other adverse events, including infection and device failure, were also common during longterm LVAD support. These late adverse events may contribute to the development of late RHF as a chronic aggravating factor.…”
Section: Figurementioning
confidence: 99%
“…Indeed, patients in the RHF group more frequently required re-admission due to cardiac tachyarrhythmia that may lead to worsening right ventricular function. 17 Other adverse events, including infection and device failure, were also common during longterm LVAD support. These late adverse events may contribute to the development of late RHF as a chronic aggravating factor.…”
Section: Figurementioning
confidence: 99%
“…With the older generation HeartMate LVAD, VA after LVAD placement was thought to involve substrate around the apical inflow cannula in many cases, but analysis was largely based on 12 lead EKG localization . Small, early series of endocardial VT ablation after LVAD placement suggested that VT is not associated with the apical inflow cannula in a majority of cases . More recent, larger series including continuous flow LVAD models have confirmed that late VT is often associated with pre‐existing intrinsic scar remote from the inflow cannula, and catheter ablation in these areas terminates over half of induced VT, whereas cannula‐associated arrhythmia accounted for only 9% to 24% of cases …”
Section: Discussionmentioning
confidence: 99%
“…1 In patients with ischemic cardiomyopathy, re-entrant VT can often be ablated endocardially near areas of electric scar associated with previous myocardial infarction. However, in nonischemic cardiomyopathy, epicardial distribution of scar and sites of origin for VT is comparatively more frequent.…”
Section: Discussionmentioning
confidence: 99%